An Updated View on Water Masses on the pan‐West Greenland Continental Shelf and Their Link to Proglacial Fjords. Issue 2 (8th February 2020) - Rysgaard, S.; Boone, W.; Carlson, D.; Sejr, M. K.; Bendtsen, J.; Juul‐Pedersen, T.; Lund, H.; Meire, L.; Mortensen, J.
Abstract: The accelerated melt of the Greenland Ice Sheet has been linked to a sudden increase in the presence of warm subsurface coastal water in west Greenland. Yet pathways of warm coastal water along the entire west Greenland coast have remained largely unstudied. Here we present the first, near‐synoptic hydrographic observations at both the continental slope and fjord entrances of the west Greenland coastal system from Cape Farewell (59°N) to Melville Bay (75°N) in summer 2016. We observed a distinct north‐south division in the water mass distribution in west Greenland, approximately partitioned by the northern part of Davis Strait, and a division between the continental slope and fjord entrances. Waters from the regional southern freshwater source with origin in the East Greenland Current that rounds Cape Farewell are not observed to enter Baffin Bay. The regional heat source transported by the West Greenland Current is blocked by Southwest Greenland Coastal Water in the south but the deep connections in the north allow warm deep Subpolar Mode Water to enter fjords. Furthermore, we observed cold and relative saline Baffin Bay Polar Water over the inner part of the banks, periodically reaching as far south as 64°N, suggesting the presence of an undescribed southward current at the Southwest Greenland continental shelf. Key Points: The regional southern freshwater source transported northward along the Greenland west coast did not enter Baffin Bay during summer 2016 North of Davis Strait, warm deep Subpolar Mode Water may enter the deep silled fjords unobstructed Baffin Bay Polar Water is observed on the Southwest Greenland coast as far south as 64°N suggesting a seasonal southward coastal current